Web application for monitoring health index of electrical power transmission lines and cables - Solemon B.; Deris A.M.; Salleh F.H.; Omar R.C.; Baharuddin I.N.Z. (Alpha Publishers, 2023)
Infrastructure asset management is one of the major concerns in Tenaga Nasional Berhad (TNB). Failure of any transmission tower would cause disruption in power supply affecting a huge area, huge economic losses to TNB, and danger to maintenance workers and the public. Thus, efficient maintenance and management system for transmission towers is crucial. To monitor the transmission towers and lines condition, a group of researchers and engineers in TNB have embarked on a research to formulate a systematic framework to determine indicator statuses of power transmission lines and a web-based system to monitor the transmission lines and cables conditions based on the statuses. The system is known as TNB Transmission Line and Cables Health Index (LCHI). In LCHI, the elements to determine condition of transmission lines and cables are insulator, conductor, spacer/damper, mid-span joint, tower footing resistance, right of way, ground clearance, slope condition, bracing and crossarm, cross-linked polyethylene cable and oil-filled cable. These elements can be classified into three components: electrical/mechanical, surrounding environment and structural. This paper explains the health index determination framework and the evolutionary prototyping approach adopted to develop the system. Also, it explains the process flow, components and elements used to determine health index of the transmission lines and cables. This is followed by explanation on the context and main features of LCHI system. In the energy sector generally, the system plays an important role in prioritizing maintenance, refurbishing or replacing transmission towers to avoid power supply disruption. 2020 Alpha Publishers.